Film Coating of Nifedipine Extended Release Pellets in a Fluid Bed Coater with a Wurster Insert - de Souza, Luciane Franquelin Gomes (Hindawi Publishing Corporation, 2014)
The objective of this work was to study the coating process of nifedipine extended release pellets using Opadry and Opadry II, in a fluid bed coater with a Wurster insert. The coating process was studied using a complete experimental design of two factors at two levels for each polymer. The variables studied were the inlet air temperature and the coating suspension flow rate. The agglomerate fraction and coating efficiency were the analyzed response variables. The air temperature was the variable that most influenced the coating efficiency for both polymers. In addition, a study of the dissolution profiles of coated and uncoated pellets using 0.5% sodium lauryl sulfate in simulated gastric fluid without enzymes (pH 1.2) was conducted. The results showed a prolonged release profile for the coated and uncoated pellets that was very similar to the standards established by the U.S. Pharmacopoeia. The drug content and the release profiles were not significantly affected by storage at 40°C and 75% relative humidity. However, when exposed to direct sunlight and fluorescent light (light from fluorescent bulbs), the coated pellets lost only 5% of the drug content, while the uncoated ones lost more than 35%; furthermore, the dissolution profile of the uncoated pellets was faster.